THE DETERMINATION OF NOBLE WOMEN’S MAHR BASED ON EDUCATION LEVEL: A STUDY IN BONDER VILLAGE, PRAYA BARAT, CENTRAL LOMBOK - Hanif Danu Paksi; Sainun; Geitza Zahra Sofa (QANUN: Journal of Islamic Laws and Studies, 2025)
This study analyzes the aspects of Islamic family law related to the determination of mahr for noble women based on their education level, focusing on a case study in Bonder Village, Praya Barat District. The study aims to examine the practice of granting mahr to noble women based on their education level and the community's perspective on this phenomenon. This research employs a qualitative approach with an empirical method, utilizing interviews, observations, and documentation for data collection, while data analysis is conducted through editing, classification, analysis, and conclusion. The findings indicate that the practice of determining mahr for noble women in Bonder Village is influenced by the level of education they have attained, where higher education levels correspond to higher mahr values. Furthermore, community views on this matter tend to be inconsistent with Islamic teachings, as excessively high mahr contradicts the principle emphasized in the Qur'an: "Give the women (you marry) their due mahr graciously."